2019 IEEE 16th International Symposium on Biomedical Imaging (ISBI 2019) 2019
DOI: 10.1109/isbi.2019.8759266
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Training Stain Invariant CNNS

Abstract: An important part of Digital Pathology is the analysis of multiple digitised whole slide images from differently stained tissue sections. It is common practice to mount consecutive sections containing corresponding microscopic structures on glass slides, and to stain them differently to highlight specific tissue components. These multiple staining modalities result in very different images but include a significant amount of consistent image information. Deep learning approaches have recently been proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…To mitigate the lack of data and increase the dataset diversity, we used the Augmentor [20] library to perform data augmentation on our dataset. We privilege transformations which could appear in reality due to human or mechanical manipulations as in [21]: 1 The YOLOv3 network downsamples input images by 32. Hence, the input images must be multiple of 32.…”
Section: Data Augmentationmentioning
confidence: 99%
“…To mitigate the lack of data and increase the dataset diversity, we used the Augmentor [20] library to perform data augmentation on our dataset. We privilege transformations which could appear in reality due to human or mechanical manipulations as in [21]: 1 The YOLOv3 network downsamples input images by 32. Hence, the input images must be multiple of 32.…”
Section: Data Augmentationmentioning
confidence: 99%
“…Specifically, pathology images have stain variations 19 while MRIs are susceptible to varying magnetic fields and contrast agents 20 . Such intra- or inter-dataset variations cause the training and test dataset to have different distributions, resulting in a domain-shift which impacts model generalization 21 22 . Diversifying the training data by creating larger datasets is a possible solution, but recent medical imaging studies 21 23 24 have shown that it does not guarantee improved generalization.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the earlier efforts that utilized DL used samples obtained at a single institution and lacked independent external validation and performance comparison with a radiologist [13][14][15][16][17]. Despite the high-representative capacity of DL models, several authors have recently criticized the generalizability of DL models across datasets derived from different domains (e.g., MRI obtained with different MRI scanners or at different institutions) [20,21].…”
Section: Introductionmentioning
confidence: 99%